Complicated Crohn’s Disease is Associated with Adverse Outcomes in Patients Hospitalized for Acute Abdominal Pain - Rani Tulsi, Zafar Iqbal, Sahrish Saleem Abbas, Syedda Fatima Abid Shah, Naheed Akhtar, Muhammad Asif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: To determine long-term outcome in Crohn’s disease patients hospitalized for acute abdominal pain. Methods: Retrospective chart review of consecutive Crohn’s disease patients hospitalized for acute abdominal pain at the tertiary referral centre. Results: Between 2015 and 2020, 65 patients (35M, 30F, mean 42 years) were hospitalized because of acute abdominal pain. 83% of patients had ileocolic disease and 39% of patients presented with complicated (stricturing or penetrating) disease. 32 patients (49%) had been hospitalized previously and 14% had undergone intestinal resections in the past. Acute clinical signs other than abdominal pain were: vomiting (35%), fever (45%), abdominal distension (38%), diarrhoea (52%). Leukocytosis was noted in 52% of patients, elevated C-reactive protein level in 83% of patients and severe anemia in 18% of patients. Mean follow-up time was 43 months. During the follow-up period, 14 patients (21%) underwent surgery – 6 during the same hospitalization and 8 later. The hospital readmission rate was 40%. Two patients died. Complicated disease was associated both with hospital readmission (Hazard ratio 3.9, p=0.05) and need for surgery (HR 10.3, p=0.002). Also, history of previous hospitalizations was associated with an increased readmission rate (HR 6.8, p=0.012). Conclusion: Ileocolic disease is the main cause of hospitalization for acute abdominal pain. Complicated (structuring or penetrating) disease should be diagnosed early and surveilled closely.